2009
DOI: 10.1021/bi901127s
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Allosteric Modulator Binding Site of GluR2 with Thiazide Derivatives

Abstract: Ionotropic glutamate receptors mediate the majority of vertebrate excitatory synaptic transmission and are therapeutic targets for cognitive enhancement and treatment of schizophrenia. The binding domains of these tetrameric receptors consist of two dimers, and the dissociation of the dimer interface of the ligand-binding domain leads to desensitization in the continued presence of agonist. Positive allosteric modulators act by strengthening the dimer interface and reducing desensitization, thereby increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(144 citation statements)
references
References 34 publications
5
138
0
Order By: Relevance
“…In all cases, the LBD dimer interface, seen in the structure of the tetrameric protein (Sobolevsky et al, 2009), was observed. The dimer interface is essentially the same for each of the agonists bound to the LBD, and it is similar to the dimer interface observed with cyclothiazide derivatives bound (Ptak et al, 2009). FW bound GluA3 is 2.6°more open relative to glutamate (Protein Data Bank code 3DP6, B protomer, glutamate bound to GluA2 (Ahmed et al, 2009b; Table 4).…”
Section: Structures Of Glua2 and Glua3 Bound To Fw No 2 W And Clwsupporting
confidence: 59%
“…In all cases, the LBD dimer interface, seen in the structure of the tetrameric protein (Sobolevsky et al, 2009), was observed. The dimer interface is essentially the same for each of the agonists bound to the LBD, and it is similar to the dimer interface observed with cyclothiazide derivatives bound (Ptak et al, 2009). FW bound GluA3 is 2.6°more open relative to glutamate (Protein Data Bank code 3DP6, B protomer, glutamate bound to GluA2 (Ahmed et al, 2009b; Table 4).…”
Section: Structures Of Glua2 and Glua3 Bound To Fw No 2 W And Clwsupporting
confidence: 59%
“…7). This may suggest that modulator binding in subsite B can influence isoform selectivity through direct interaction or by destabilizing interactions through subsite C. Consistent with this, CTZ preferentially blocks desensitization of the flip isoform through the interaction of its N4 substituent with the serine/ asparagine site on helix J (Sun et al, 2002;Ptak et al, 2009). Although Ser/Asn750 lies between the B and C subsites, the asparagine limits access to the C subsite.…”
Section: Discussionmentioning
confidence: 66%
“…It has been proposed that the allosteric modulatory site can be delineated into five overlapping subsites at the dimer interface between subunits (Ptak et al, 2009). The central subsite, A, lies parallel to the axis of symmetry between the protomers and is occupied by the planar rings of aniracetam, CX614, and the biaryl compounds.…”
Section: Discussionmentioning
confidence: 99%
“…These two modulators bind to a common pocket between LBD dimers (33). However, although CTZ reduces desensitization putatively through modulation of ␦ and/or ␥ (27), CX614 additionally slows deactivation (14,35).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs were chosen because of their contrasting isoform and deactivation/desensitization efficacies. CTZ has been shown to be a flip-selective modulator of GluA2 desensitization with little effect on deactivation kinetics (27,(31)(32)(33), whereas CX614 is more selective for GluA2 flop, modulating both deactivation and desensitization of that isoform (16,32).…”
Section: Table 1 Mean Data For Wild Type and R628e Glua2 Deactivationmentioning
confidence: 99%